THE ROLE OF QUALITATIVE APPROACHES IN DESIGNING INDIVIDUALIZED CURRICULUM PLANS FOR CHILDREN WITH SPECIAL NEEDS - El-sabagh, Mennatallah; Susetyo, Budi; Rochyadi, Endang; Tarsidi, Iding (JPI (Jurnal Pendidikan Inklusi), 2025)
This paper examines the role of qualitative approaches—such as observation, interviews, and case studies—in designing individualized curriculum plans for children with special needs. Using a conceptual and literature-based method, the study aims to highlight how qualitative data help educators understand learners’ unique sensory, cognitive, and emotional profiles. The findings show that these approaches support the development of flexible and adaptive instructional strategies, enhancing student engagement and academic progress. Although the paper does not include empirical research, it provides practical insights for integrating qualitative tools into individualized education programs (IEPs). This contributes to promoting inclusion and educational equity by ensuring curriculum plans are responsive to diverse learner needs.